Low body mass and high-quality sleep maximize the ability of aerobic fitness to promote improved cognitive function in older African Americans. Issue 4 (19th May 2022) - Fausto, Bernadette A.; Gluck, Mark A.
ABSTRACT : Objectives: Because African Americans are at elevated risk for cognitive decline and Alzheimer's disease, it is important to understand which health and lifestyle factors are most important for reducing this risk. Obesity and poor sleep quality are common in lower-income, urban African Americans and have been linked to cognitive decline in older age. Fortunately, increasing aerobic fitness via regular exercise can improve cognitive function. This study sought to (1) examine the cross-sectional relationship between aerobic fitness and cognitive function in older African Americans, and (2) determine whether body mass index and sleep quality moderated the relationship between aerobic fitness and cognition. Design: 402 older African Americans, ages 60–90 (84% female, mean education level = 14 years) completed neuropsychological testing, computerized behavioral tasks, physical performance measures, and health and lifestyle questionnaires. Hierarchical linear regressions were performed to determine associations between aerobic fitness and cognition and whether body mass index and sleep quality moderate the fitness-cognition relationship while controlling for age, sex, education, depressive symptoms, and literacy. Results: Higher aerobic fitness levels were significantly associated with better executive function. The relationships between fitness and hippocampal-dependent cognitive functions (learning and memory, generalization) were attenuated in those who are obese (body mass index ≥ 30 kg/m 2 ) or rated their sleep quality as poor, p s < .05. Conclusion: Our results suggest that while exercise and associated improvements in aerobic fitness are key for improved cognition, these benefits are maximized in those who maintain low body weight and get sufficient, high quality sleep. Exercise programs for older African Americans will be most effective if they are integrated with education programs that emphasize healthy eating, weight control, and sleep hygiene and conceptualize individuals as part of their broader social and environmental context.